Simulating on Passengers Coordination with Distribution Service in Railway Station - Qian LI; Limin JIA; Changxu JI; Jianling Huang; Zhongyuan Jiang (Institute of Advanced Engineering and Science, 2013)
Based on the hierarchical characteristics of passengers transfer behavior and the state-dependent queuing model, the D-M/G/C/C queuing network simulation model was put forward for simulating the coordination of subjective passenger behavior and objective distribution environment. Then, the generation method and algorithm of the model is elaborated. In case study, the simulation results are consistent with the actual states of passenger outbound process. So, it is a practical simulation tool for analyzing the dynamic situations of passengers use facilities. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1912